Method and Truth - Moberly, Walter (Harvard theological review, 2020)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0017816020000267/resource/name/firstPage-S0017816020000267a.jpg